2018
DOI: 10.1016/j.jpainsymman.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Palliative Drug Treatment in the Last Days of Life—A Systematic Literature Review

Abstract: There is a lack of evidence concerning the effectiveness and safety of palliative drug treatment in dying patients, and the reviewed evidence provides limited guidance for clinicians to assist in a distinct and significant phase of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 52 publications
(110 reference statements)
0
27
0
2
Order By: Relevance
“…End-of-life caredpharmacological symptom control Adults Outcome: quality of care 1 SR 123 One review examining a range of palliative interventions and outcomes concluded that there is a lack of evidence concerning the effectiveness and safety of palliative drug treatment in dying patients. No evidence was found for scopolamine hydrobromide and atropine for death rattle; some evidence was found supporting the use of morphine and midazolam for dyspnea, anxiety, or terminal restlessness; and some support was found for morphine, diamorphine, and fentanyl for pain.…”
Section: (S Im)mentioning
confidence: 99%
“…End-of-life caredpharmacological symptom control Adults Outcome: quality of care 1 SR 123 One review examining a range of palliative interventions and outcomes concluded that there is a lack of evidence concerning the effectiveness and safety of palliative drug treatment in dying patients. No evidence was found for scopolamine hydrobromide and atropine for death rattle; some evidence was found supporting the use of morphine and midazolam for dyspnea, anxiety, or terminal restlessness; and some support was found for morphine, diamorphine, and fentanyl for pain.…”
Section: (S Im)mentioning
confidence: 99%
“…The most commonly prescribed drugs were generally opioids and benzodiazepines, although anti‐cholinergics were also frequently prescribed at SGH. Whilst there is no convincing evidence for the use of anti‐cholinergics in terminal respiratory secretions, the practice is quite common in palliative care …”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is no convincing evidence for the use of anti-cholinergics in terminal respiratory secretions, the practice is quite common in palliative care. 19 Cessation of observations and non-essential medications was quite low, likely reflecting the acute hospital environment where observations are not just routine but, at times, even required (unless otherwise documented).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of morphine on alleviating dyspnea has been well investigated [26]. Because of the deteriorated capacity of drug metabolism and excretory abilities during the end-of-life period, the administration of morphine requires careful monitoring of adverse events (e.g., impaired conscious state and decreased respiration rate) [26].…”
Section: Dyspneamentioning
confidence: 99%
“…The effect of morphine on alleviating dyspnea has been well investigated [26]. Because of the deteriorated capacity of drug metabolism and excretory abilities during the end-of-life period, the administration of morphine requires careful monitoring of adverse events (e.g., impaired conscious state and decreased respiration rate) [26]. Given the concerns of those adverse events, physicians are less confident with prescribing opioids for dyspnea than for pain, which can result in the undertreatment of dyspnea [27].…”
Section: Dyspneamentioning
confidence: 99%